(untitled) (Editora Impacto Científico, 2025)
The objective of this study is to present the results of some actions carried out by the extension project of the Fashion Design course at UEM, entitled "Social Media: Sharing and Creating Fashion Content," which aims to promote integration between the university and society through the creation of digital content. The qualitative research used photographic records, participant accounts, and an annual report as sources of analysis, covering the period from March 2024 to August 2025. The activities involved students from the Fashion Design course at the State University of Maringá (UEM) and some sectors of society located in the city of Cianorte–PR. The results highlight the relevance of university extension in the academic, social, and civic education of students, by enabling the practical application of curricular knowledge, in addition to providing participants with experiences of personal growth. It is concluded that the actions carried out contributed to strengthening the university’s social commitment. DOI: https://doi.org/10.56238/edimpacto2025.090-073